PERTANGGUNGJAWABAN PIDANA CV. PERMATA BUNDAATAS TINDAK PIDANA KECELAKAAN LALU LINTAS OLEH PENGEMUDI BERDASARKAN UNDANG UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI KOTA DURI - Weli Gusnanda; Mukhlis R; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Land transportation can reach all points in Indonesia. Thus, transportation is a necessity that cannot be separated from the growth of society, especially in this era of globalization, which all require a faster media. Transportation facilities in Indonesia certainly play an important and strategic role so that their implementation is controlled by the state, and their guidance is carried out by the government. Thus, it is hoped that the existence of transportation will be able to influence all aspects of life, especially the smooth flow of trade and development results. And the existence of traffic has a function in accordance with the objectives of national development, namely to form a just and prosperous society both materially and spiritually based on Pancasila and the 1945 Constitution of the Republic of Indonesia.The problem that the writer makes the basis of this research is how the criminal responsibility of CV. PermataBunda for the crime of traffic accidents by the driver of CV. PermataBunda and What are the obstacles faced in law enforcement for traffic accidents by drivers of CV. Jewel Mother in the City of Duri?This type of research used by the author is sociological legal research, which is also called doctrinal legal research. This normative research is a study that discusses legal principles, legal systematics, the level of legal synchronization, legal history and legal comparisons. From this sociological legal research, the author is interested in conducting research using legal systematic criteria. The results of this study are firstly that corporate criminalization is often associated with financial problems, but in principle it has more than that. This is supported by the fact that currently a business entity is formed to achieve prosperity, whether it is implemented by the government or by an individual or a group. The same is the case with one of the public transportation corporations located in Mandau sub-district, Duri city, namely CV PermataBunda, which in terms of solving problems that occur in traffic accidents carried out by one of the drivers or drivers, in this case the settlement made by CV PermataBunda Not at all affected by the criminal action, in this case CV PermataBunda only provides compensation to the victim but the one being convicted is the driver or the driver, in accordance with the provisions of Law Number 29 of 2009 Article 315, CV PermataBunda should also be convicted by punishment in the form of imprisonment or a fine as well as suspension of public transport permits. The two factors that influence law enforcement on traffic accidents by CV drivers. The gems of the Mother in the City of Duri are; legal factors, law enforcement factors, facilities and infrastructure factors and supporting facilities as well as community factors.Keywords: Transportation, Public Transport, accidents